Conductivity in SnO2 polycrystalline thick film gas sensors: Tunneling electron transport and oxygen diffusion - Aldao, Celso Manuel (2014)
Conduction mechanisms in polycrystalline SnO2 thick sensing films were investigated by means of DC electrical resistance during heating?cooling cycles. Samples were maintained at relatively high temper- atures in H2 or O2 ambient atmospheres before performing electrical measurements under vacuum or before performing XPS measurements in order to determine band bending. Results suggest that inter- grains present Schottky barriers that are responsible for the observed conductivities regardless of gas pre-treatment. Oxygen diffusion modulates barrier widths affecting conductivity through tunneling transport. The electrical response to subsequent exposure to an oxygen atmosphere is consistent with our interpretation.